Back Cover: AIE‐based drug/gene delivery system: Evolution from fluorescence monitoring alone to augmented therapeutics. Issue 6 (26th December 2022) - Sun, Jie; He, Xuewen
Abstract : In the evolution of AIE‐based drug and gene delivery systems, the light‐up AIEgens start in real‐time monitoring of the delivery processes and evaluation of therapeutic responses of drug/gene; The delicate structural design of AIEgens to form high‐level carriers remarkably enhances the drug/gene delivery efficiency; Further, endowed with multifunctionalities, AIEgens are synergized in multimodality therapy to achieve augmented therapeutic efficiency(e282 ).